MEDIA LOKAL DAN INDIVIDUASI POLITIK - Widodo, Suko (Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2014)
This article highlights the personalization of politicians and howthe roles of political parties start waning in terms of democratization in Indonesia. In this context, the media, including local media, play a central role. Based on the analysis of the media, the agenda of media is often prepared on the interests of capital’s owner as the party who posses power. On the contrary, public agenda which emergesbased on public’s feed back, in which it should theoretically affect the agenda of the media, tends to be neglected. The neglection of the public agenda cannot be separated from the shift of the meaning of the media in the modern era which tends to run a market-driven journalism. The system of political competition in both local and national legislativeand presidentialelections has brought merely about implications of personal characterization, comparingto the substantial role of political parties. In this context, the role of local media as a platform of candidate characterization is irrefutably essential.